Reduced root cortical burden improves growth and grain yield under low phosphorus availability in maize - Galindo‐Castañeda, Tania; Brown, Kathleen M.; Lynch, Jonathan P. (Plant, cell and environment, 2018)
Root phenes and phene states that reduce the metabolic cost of soil exploration may improve plant growth under low phosphorus availability. We tested the hypothesis that under low phosphorus, reduced living cortical area (LCA) would increase soil exploration, phosphorus capture, biomass, and grain yield. Maize genotypes contrasting in LCA were grown in the field and in greenhouse mesocosms under optimal and suboptimal phosphorus regimes. Percent LCA in nodal roots ranged from 25% to 67%. Plants with 0.2 mm2 less LCA under low phosphorus had 75% less root segment respiration, 54% less root phosphorus content, rooted 20 cm deeper, allocated up to four times more roots between 60 and 120 cm depth, had between 20% and 150% more biomass, 35–40% greater leaf phosphorus content, and 60% greater grain yield compared with plants with high LCA. Low‐LCA plants had up to 55% less arbuscular mycorrhizal colonization in axial roots, but this decrease was not correlated with biomass or phosphorus content. The LCA components cortical cell file number and cortical cell size were important for biomass and phosphorus content under low phosphorus. These results are consistent with the hypothesis that root phenes that decrease the metabolic cost of soil exploration are adaptive under phosphorus stress. Living cortical area of maize root tissue is reduced under suboptimal phosphorus availability through the production of aerenchyma. Using greenhouse and field‐grown maize genotypes with contrasting living cortical area, we tested the hypothesis that plants with reduced living cortical area would have decreased respiratory carbon and phosphorus demand, greater soil exploration, and greater phosphorus capture. Genotypes with reduced living cortical area had reduced root segment respiration and phosphorus content, greater shoot biomass, phosphorus content, and grain yield under suboptimal phosphorus availability. Our results support the hypothesis that reduced living cortical area may have adaptive value under suboptimal phosphorus availability.